Diethyl 4-hydroxy-4-methyl-6-oxo-2-phenylcyclohexane-1,3-dicarboxylate - Hoong-Kun Fun; Madhukar Hemamalini; Mahesh Padaki; Arun M Isloor (Acta Crystallographica Section E, 2010)
In the title molecule, C19H24O6, the cyclohexanone ring adopts a chair conformation. The dihedral angle between the phenyl ring and the best plane through the six atoms of the cyclohexanone ring is 89.68 (7)°. In the crystal structure, molecules are linked via pairs of intermolecular O—H...O hydrogen bonds into centrosymmetric dimers and these dimers are connected by C—H...O interactions into columns down the a axis.